Keberadaan Bakteri Salmonella sp Pada Telur Ayam Di Pasar Tradisional Kota Palembang Sumatera Selatan - Aryani, Aryani; Marmaini, Marmaini; Novianti, Dewi (Indobiosains, 2025)
Eggs are a product of animal origin that is famous as a high source of protein compared to other protein source ingredients. Damage that can cause a decrease in egg quality is caused by microorganisms, one of which, bacteria that can contaminate eggs is Salmonella sp. This study aims to analyze the presence of Salmonella sp bacteria in chicken eggs sold in several traditional markets in Palembang City. This study used 6 samples of chicken eggs from 3 traditional markets with a simple random sampling method. The test results of all positive egg samples contained Salmonella sp. This shows that the quality of eggs sold at the Palembang Traditional Market does not meet the requirements of the Indonesian National Standard, which is negative/25 grams.     Keywords: Salmonella sp, chicken egg, traditional market.